Electric Power Substations Engineering. - McDonald.,John D.; McDonald, John D. 1951- (Boca Raton : CRC Press, 2012)
"The electric power substation, whether generating station or transmission and distribution, remains one of the most challenging and exciting fields of electric power engineering. Recent technological developments have had tremendous impact on all aspects of substation design and operation. The objective of Electric Power Substations Engineering is to provide an extensive overview of substations, as well as a reference and guide for its study. The chapters are written for the electric power-engineering professional for detailed design information, as well as for other engineering professions (e.g., mechanical, civil) who want an overview or specific information in one particular area"--
include index.
Keywords: Electric substations; TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Power Resources / Alternative & Renewable; TECHNOLOGY & ENGINEERING / Power Resources / Electrical